A model to estimate the effect of variables causing erosion in wind turbine blades. Issue 9 (8th February 2021) - Prieto, Raúl; Karlsson, Timo
Abstract: The quantification of the severity of erosion in wind turbine blades is challenging due to the many aspects involved, including meteorology, aerodynamics, materials science, and wind turbine dynamics. A complete model relies on several building blocks, which cover the characterization of precipitation and aerosols, the trajectories of droplets and particles, the operational settings of the wind turbine, and finally the structural response of the leading edge to the large number of impacts across a spectrum of particle sizes and impacts speeds. This paper presents a multidisciplinary model, defining magnitudes representative of erosion severity and formulating their dependencies. The method uses the formula for the erosion incubation time as defined by Springer. The model incorporates the effect of wind velocity and density, particle size, and erosion intensity, and it allows four erosion mechanisms to be considered: rainfall, snowfall, sea spray, and fog. Comparison of the predicted erosion incubation time versus blade inspections shows good qualitative agreement. The equations from the model suggest that the characterization of atmospheric conditions at the site is essential for an accurate estimation of the severity of erosion. Equally important are the material properties, and the impingement process at the leading edge.